Sphenoid sinus foreign body following airbag deployment in the United States: a case report - Birk J. Olson; Joseph B. Vella; Justin P. McCormick (Journal of Trauma and Injury)
We report a unique case of penetrating foreign bodies following a motor vehicle accident with airbag deployment. The patient presented with evidence of facial trauma and was found to have three retained foreign bodies on imaging. Notably, one foreign body was within the sphenoid sinus. This foreign body was removed uneventfully through endoscopic sinus surgery. The patient was doing well at follow-up visits. We concluded that the foreign bodies were steering wheel accessories, which detached upon airbag deployment and penetrated the patient’s face. This case report is intended to inform the public regarding the dangers of placing accessories on a steering wheel.